A Personal History in Black – A Portrait of a Historian in her Youth in Belgrade (1979-1991) - Jelena Mrgić (Etnoantropološki Problemi, 2025)
This paper originated from a draft and visual presentation for a scientific conference, aiming to relate a personal story as part of the fashion history of the socialist Serbia/Yugoslavia. The approach takes myself both as a witness and a historian, making the narrative inevitably biased, intimate and sentimental. Nevertheless, the presented material evidence (my fashion sketches, personal photographs) and my recollections of the ‘city’ and its ‘heterotopias’ at that time (my map), could serve as valid testimonies to a late socialist way of life. Twelve years may and may not seem like a long period, but those were the formative years of my life, when I pursued and then gave up studying costume and fashion design, choosing the greater certainty in studying history. I have discerned two distinct stages marked by dominant colors – brown childhood versus black and ‘gothic’ youth in high school. Growing up in Tito’s and post-Tito’s Yugoslavia was not without awareness of class differences, social mobility did exist, and I was not significantly limited in school options, since I excelled in my primary school.